2019
DOI: 10.1371/journal.pone.0226473
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and NRAS mutational gene profile of metastatic colorectal cancer patients in Jordan

Abstract: BackgroundA constitutively active RAS protein in the absence of stimulation of the epidermal growth factor receptor (EGFR) is the result of mutations in KRAS and NRAS genes. Mutations in the KRAS exon 2 and outside exon 2 have been found to predict the resistance to anti-EGFR monoclonal therapy. A substantial proportion of metastatic colorectal cancer cases (mCRC) exhibit RAS mutations outside KRAS exon 2, particularly in KRAS exon 3 and 4 and NRAS exons 2 and 3. No data about RAS mutations outside KRAS exon 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Additionally, similar to the results of other authors [24,25] we noticed that mutations G12D and G12V are the most prevalent in the Serbian population. We found that the frequency of mutations in codons 59, 117 and 146 were 1.5%, which is in concordance with the study of Awidi et al [26] while a higher prevalence of the mutation in codon 146 was observed in patients from Thailand, where 8.3% of them had this mutation [27]. Many authors evaluated correlations between mutations in KRAS, age and sex of patients with clinicopathological characteristics of CRC and some of the results indicate that both tumor location and KRAS status play important roles in the prognosis of CRC patients [19,20,28].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, similar to the results of other authors [24,25] we noticed that mutations G12D and G12V are the most prevalent in the Serbian population. We found that the frequency of mutations in codons 59, 117 and 146 were 1.5%, which is in concordance with the study of Awidi et al [26] while a higher prevalence of the mutation in codon 146 was observed in patients from Thailand, where 8.3% of them had this mutation [27]. Many authors evaluated correlations between mutations in KRAS, age and sex of patients with clinicopathological characteristics of CRC and some of the results indicate that both tumor location and KRAS status play important roles in the prognosis of CRC patients [19,20,28].…”
Section: Discussionsupporting
confidence: 93%
“…36 Other cohort studies have demonstrated similar results which are consistent with our findings. 37,38 While KRAS G12D mutation has been consistently reported to be the most common KRAS mutation, KRAS G12C mutation, which is now potentially amenable to pharmacotherapy, 39 accounts for 4% of mutations in our study. BRAF is the most frequently mutated protein kinase of the RAF family, accounting for about 10% of metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 71%
“…(6,5%), G12S (3,3%), G12C (2,2%), K117N or A146V (10,85%) and Q61X (5,4%) (Awidi et al, 2019). In a study conducted by Baskin and colleagues in 2014, ratio of KRAS mutations in codon 12 and codon 13 were evaluated (Baskin et al, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%